ANALISIS PEMBERDAYAAN MASYARAKAT NELAYAN DI DESA PAMBANG PESISIR KECAMATAN BANTAN KABUPATEN BENGKALIS - Nurman M. Herizal; Maulida Yusni; Aqualdo Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine to analyze the empowerment program that has been carried out to increase the income of the fishing community in the Pambang Pesisir village, Bantan District, Bengkalis Regency. The object of research is the fishing community in the Pambang Pesisir village. The sampling method used in this study was the simple random sampling technique. This study uses secondary data and primary data taken from the results of distributing questionnaires. The data obtained were analyzed using quantitative descriptive analysis. The results showed that several empowerment activities that have been carried out by the government in Pambang Pesisir Village include; boat assistance for fishermen, assistance for fishing gear (nets), cultivation of catfish and other freshwater fish, establishing institutions for fishermen such as cooperatives, and conducting training and guidance to fishing communities. The empowerment activities carried out by the government have not been maximal in their implementation. On the one hand, fishermen are also quite helped by these assistance and activities, but the implementation is still inefficient, due to the lack of seriousness of the government in carrying out these empowerment activities, which is still lacking in equity in assistance. Therefore, empowerment has less effect on the income level of fishermen in Pambang Pesisir Village.Keywords: Empowerment of fishing communities, income